V ozhidanii nashego budushchego sotrudnichestva (Waiting for our future collaboration) (ENTHYMEMA, 2025)
In memory of Peter Steiner.
Keywords: Peter Steiner; Russian Formalism; Czech Structuralism; Theory of Literature